Kalanchoe ×sogae (Crassulaceae subfam. Kalanchooideae) derived from Kalanchoe lateritia × K. sexangularis, with notes on the inheritance of hairiness and resistance against phytophagous insects in Kalanchoe hybrids - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2022)
The hybrid between Kalanchoe lateritia and K. sexangularis (Crassulaceae subfam. Kalanchooideae) is described as K. ×sogae. Like K. lateritia, virtually all plant parts of K. ×sogae are covered in a fine indumentum, but with the indumentum being less substantial in the case of this nothospecies. The leaves and stems of material of K. ×sogae are bright red-infused, especially when growing in full sun. This hybrid shows considerable horticultural potential and is more resistant against phytophagous insects than K. sexangularis.